ANALYSIS OF REGIONAL MIGRATION DISPARITIES IN ROMANIA - Andreea STROE; Andreea-Oana ENACHE (Challenges of the Knowledge Society)
Migration is a complex phenomenon, highly studied globally. Thus, the analysis of the population mobility process is performed using an interdisciplinary approach, with strong links in sociology, history, economics, geography, demography and even psychology. All disciplines involved in the analysis of the phenomenon target different aspects of population migration, define the decision underlying the migration of individuals and build the image of the impact that the phenomenon has on the actors involved. Emigration and immigration became important aspects of the Romanian society in the last decade. The present paper focuses on the regional migration phenomenon in Romania, between 1991 and 2019. The objective of the research is to characterize from a quantitative point of view the migration flows in and from Romania. Moreover, ARDL models are used to analyse the impact of the GDP in the migration decision. This analysis highlighted the fact that people who decide to emigrate are from all age groups and their decision is based on socio-economic considerations, these categories being attracted by well-paid jobs. The link between the number of emigrants and the evolution of GDP in Romania made with the help of a regression equation, which showed that there is a weak link between these variables, confirms once again that the evolution of gross domestic product did not change the decision of emigration to Romania.